Consórcio de Segurança Alimentar e Desenvolvimento Local (CONSAD): análise de múltiplos fluxos do CONSAD Iguatemi - MS - Rocha, Flávio de Matos (2012)
The Consortium for Food Security and Local Development (CONSAD) has received too much emphasis in academic and policy environment as it´s "novelty" in the field of sectoral policies. The CONSAD is characterized by different institutions, presenting itself as an intersection between food security policy, local and territorial development, so that one of its principles includes the participation of civil society. And one cannot dismiss the potential of these consortia as agents of change in local archaic structures which concentrates income and development processes. In this way, the objective of this dissertation is to analyze the origin and the institutionalization of the CONSAD as a public policy in the context of the National Food and Nutrition Security (PNSAN). Therefore, this work was organized into three perspectives. The theoretical approach trough the model of the Multiple Streams, addressing the process of building and developing PNSAN. The thematic approach, situating the emergence of CONSAD with an institutional perspective, analyzing the mechanisms that allowed the consolidation of this policy and its format as a public consortium that runs through the structure of a management council. And the empirical approach, performing a case study of CONSAD Iguatemi - MS. Among the research findings is that the achievement of the objectives of CONSAD Iguatemi MS is surrounded by operational constraints, related to lack of resources, organizational problems, some coming from the very structure imposed by the institutional design of the program. The lack of effectiveness by the actions of its members, the lack of experience and qualifications of directors to take control functions, and policy proposals at the Forum, are considered the key problems. In conclusion, to address these barriers found in this research is necessary to provide the members and advisors from CONSAD Iguatemi - MS adequate training for participatory processes, training to understand the institutional mechanisms of the consortium, training to instruct them how to seek partnerships and funding for the Consortium. Another relevant observation argues that the absence of MDS both for the interaction between governments and the Consortium and the release of resources implicate the risk of limiting the development of this policy.